Isolated Pectoralis Minor Release for Scapular Dyskinesis. Issue 7 (29th July 2014) - Provencher, Matthew; Golijanin, Petar; Gross, Daniel; Campbell, Kevin J.; Gaston, Tistia; Anthony, Shawn
Objectives: Pectoralis minor (PM) tightness has been linked to pain and dysfunction of the shoulder joint secondary to anterior tilt and internal rotation of the scapula, causing pseudo-impingement of the subacromial space. Most patients with pathologic tightness of the PM are treated successfully with non-operative treatment, yet a minority of patients experience persistent pain and dysfunction due to a pathologically tight PM. The purposes of this study are to describe the outcomes of operative release of PM tightness recalcitrant to nonoperative measures. Methods: Over a 3-year period, a total of 46 patients were enrolled (mean age 25.5, range 18 to 33) who presented with symptoms of shoulder pain, limited range of overhead motion, and inability to participate in overhead lifting activities, with examination consistent with primary abnormality of scapular dysfunction due to a tight PM with tenderness in the PM tendon. All patients underwent an extended period of physical therapy and stretching program (mean 11.4 months, range 5-23 months), and were followed with serial examinations for resolution of symptoms and scapular tilt. 6/46 (13%) patients were unable to adequately stretch the PM, and underwent isolated mini-open PM release. Outcomes were assessed with scapula protraction measurements, pain scales, and ASES and SANE score. Results: A total of 40/46 (87%) patients resolved the tight PM and scapular mediated symptoms with a dedicated therapy program (ASES 58 to 91; SANE 50 to 90, VAS 4.9 to 0.8, p<0.01). The 6/46 patients treated with isolated PM release demonstrated improvement in outcomes after failed nonoperative care (ASES 48 to 89; SANE 40 to 90.4; VAS 5.8 to 0.9, p<0.01). Overall, protraction of the scapula increased. The inferomedial scapular border was a mean of 1.2 cm from the chest wall preoperatively, and 0.3 cm postoperatively (p<0.01), similar to nonoperative responders. There were no complications and all those with isolated PM release returned to full or increased duties after release. Conclusion: In most patients, PM tightness can be successfully treated with non-operative management. However, in refractory pathologically tight PM cases, this series demonstrates predictable return to function with notable improvement in shoulder symptoms. Additional work is necessary to evaluate the long-term efficiency of isolated PM release.